FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR DALAM MATA KULIAH AKUNTANSI KEUANGAN MENENGAH I (Studi Empiris pada Mahasiswa Akuntansi Perguruan Tinggi Negeri dan Perguruan Tinggi Swasta di Semarang) - Mahmudah, Noor Aini; Ika S, Ardiani (Jurnal Akuntansi Bisnis, 2011)
Students in a College consists of a wide range of attitudes and values as an individual experience which is also a reflection of the presence of family and culture. Therefore Higher Education seeks to give a stimulant to explore and grow as well as developing potential to achieve optimal student achievement. This study aims to empirically examine and analyze the influence of study habits. ability and elfort, intellectual skills. achievements in addition to Financial Accounting Intermediate I, high school grades (achievement in high school), and college grades (achievement in Higher Education) on learning achievement in subjects Intermediate Financial Accounting I. The study population in 2010 was accounting student at Public Universities and Private University in Semarang. while the samples from this study is accounting mahasisawaforce in 2007 which is being / has been taking accounting courses with a total sample o..f 1 00 respondents. Data analysis method was used to test the quality of data that include test validity, test reliability, test the classical assumption, and test hypotheses by means of multiple regression analysis, a partial test of sign ficance (t statistic). simultaneous sign ficance test (F statistic test), and coefficient of determination (R2) to assess the independent variables in explaining changes in the dependent variable. Results of hypothesis testing showed that the variables study habits, ability and effort, intellectual skills, performance in addition to financial accounting medium I, achievement in high school (high school grades) and achievement in college (college grades) influential sign(/icant e.ffect on academic achievement in subjects Intermediate Financial Accounting 1, lvith a coefficient of determination equal to 32 percent, while 68 percent is explained by other reasons - because the other variables outside of this research.